Animal Health and Productivity Status of Cattle After The Eruption of Mount Merapi - Yulvian Sani; E S Estuningsih (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
The eruption of Merapi from October 26th to November 6th, 2010 has affected social life and environment around the Merapi. The eruption has caused destruction of land and water resources, plants, death of animals and human casualities. The lava, dust and stones released from the eruption of Merapi had caused residential destruction, casualities, agricultural land and plants destruction, and contamination of water. The eruption has directly affected 4 districts including Sleman (Yogyakarta), Magelang, Boyolali and Klaten (Central Java) categorized as Disaster Risk Area (DRA). The purpose of this assessment is to analyse the impacts of Merapi eruption in animal health and productivity in particular for dairy and beef cattle. A total of 2.828 heads of cattle was reported died during the eruption of Merapi, and 1.962 heads died at the time of eruption and 36 heads at the arrival on evacuation areas. Animal that found died including 423 heads of beef cattle (0.13%) and 2.405 heads of dairy cattle (3.2%). Clinical sains noted after the eruption were reduction of milk production, loss of appetite, diarrhoea, respiratory disturbances, mastitis and collapse. The main problems for livestock were reduction of milk production, collapse of dairy milk corporation activities and contamination of water resources. Other than dairy cattle mortality, the reduction of milk production may be caused by subclinical mastitis and environmental distress due to temperature and noise of eruption for few days. The subclinical mastitis should be further investigated to establish rehabilitation programme for dairy milk agribussiness activity in particular around the DRA of Merapi. Key words: Health, productivity, cattle, disaster, Merapi